Will blade tenderization decrease iridescence in cooked beef semitendinosus muscle? - E. Obuz; Donald H. Kropf (Kansas Agricultural Experiment Station Research Reports, 2002)
Ten beef semitendinosus muscles were divided into three sections, which were randomly assigned to one of three blade tenderization treatments (control-zero, one, or two times). Blade-tenderized muscles were cooked in a forced-air convection oven at 325° to 145°F and held for 1 min. Cooked muscles were chilled overnight at 38°F and sliced by a sharp knife. Panelists (n=19) evaluated iridescence intensity on a five-point scale (0=no iridescence, 5=very strong) and extent of iridescence (0=no iridescence, 5=81-100% affected area). Blade tenderization decreased (P<0.05) iridescence intensity from 2.37 to 2.02 and extent of iridescence from 2.18 to 1.83 (control zero vs. two passes). Cooking loss increased (P<0.05) with blade tenderization (30.4% control, 32.6% one pass, 33.7% two passes). Blade tenderization has a moderate effect on reducing iridescence.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Iridescence; Blade tenderization